IDENTIFIKASI ENDOPARASIT FESES Gallus domesticus DAN POTENSINYA SEBAGAI MEDIA BELAJAR - Anthon Yunias Aninam; Apriani Herni Rophi; Agustinus Renyoet (NOVAE GUINEA Jurnal Biologi, 2024)
Free-range chickens (Galus domesticus) are a type of pet. The obstacle faced in raising free-range chickens is the problem of endoparasites, which infect free-range chickens, causing health problems such as lethargy, paleness, and even resulting in death. Endoparasites that attack free-range chickens are studied in Platyhelminthes material in class This research aims to determine the types of endoparasites that attack free-range chickens, their prevalence, and the potential for using dry preserved preparations as a learning medium. This research is a qualitative descriptive research using random sampling. The population in this study were all free-range chickens on Mr. Agustinus Sirang's farm in Traymelyan Village, Keerom Regency, while in this study there were 10 free-range chickens on Mr. Agustinus Sirang's farm in Traymelyan Village, Keerom Regency. data was analyzed descriptively. The results of this research found 1 type of endoparasite that infects free-range chickens (Gallus domesticus), namely Ascaridia galli. The prevalence of Ascaridia galli which infects free-range chickens (Gallus domesticus) is 50% in the very frequent category. The dry preserved preparations that are made can be tested for validation to see their suitability as a learning medium., method main finding, and final conclusion. Keywords : Ascaridia galli, Endoparasites, Gallus domesticus, Potential Learning Media